Website-based Educational Games for Physical Education on Basic Football Game Technique Material for Secondary Students - Jozuna Aziz Kusuma Mukti; Muhammad Akhyar; Eka Budhi Santosa (Jurnal Teknologi Pendidikan)
The development of a web-based educational game for the teaching of Physical Education, Sports, and Health (Penjasorkes) represents an innovative approach aimed at enhancing student engagement and comprehension of fundamental soccer techniques, including passing, dribbling, and shooting. This research employs a Research and Development (R&D) methodology based on the Alessi & Trollip model, which encompasses stages of planning, design, and development. The research subjects include media experts, content specialists, Penjasorkes teachers from high schools and vocational schools, and students as end users. Data collection was conducted through observations and questionnaires, followed by qualitative and quantitative analysis. The alpha test results indicated a "very good" validation from experts and practitioners, with an average score of 89%, while the beta test conducted with students yielded an average score of 90%, demonstrating the feasibility and appeal of this media. These findings affirm that the web-based educational game can significantly boost student motivation and engagement, serving as a practical solution to the limitations of conventional learning media. Consequently, this educational game is not only pertinent to Penjasorkes instruction in high schools and vocational schools but also has the potential to serve as a model for the development of similar media in other educational contexts.